Towards Understanding Population Behaviour of Conducted Energy Weapons in Canada - Adler, Andy; Dawson, David; Marsh, Owen (CMBES Proceedings, 2012)
Our long term goal is to develop an understanding of the performance characteristics of Conducted Energy Weapons (CEW’s) which might have an effect on safety for subject or operator. In this paper we present results of the analysis of the electrical output of over 200 Conducted Energy Weapons taken over a three year period from the inventory of weapons of different police services in Canada. These results are first compared to the manufacturer’s performance specifications and then presented more broadly with respect to general electrical characteristics.